Electronic Word of Mouth as A Moderating Variable of Food Reviewer Influence on Purchasing Decisions - Nabila Cecilia Marasbessy; Jhoni Iskandar; Yoyo Indah Gunawan; Feby Evelyna; Septa Intiar (Yayasan Inovasi Kemajuan Intelektual, 2025)
This study aims to analyze and examine the influence of food reviewers on consumer purchasing decisions, as well as the role of electronic word of mouth (eWOM) as a moderating variable in this relationship. In today's digital era, food reviewers have evolved into a credible source of information that influences food preferences and shopping behavior. However, the effectiveness of this influence is not always direct, but rather depends on the extent to which the reviews are disseminated and amplified through eWOM across various digital platforms. Using a quantitative approach, data were collected from consumers who had been exposed to food reviewer reviews and made food product purchasing decisions. A moderated regression analysis (MRA) model was implemented using EViews to test the hypotheses, specifically to measure the interaction between the influence of food reviewers and eWOM. The results are expected to provide empirical evidence regarding the significance of the food reviewer variable and, more importantly, identify the critical role of eWOM in strengthening or weakening this initial influence. These findings will contribute to a deeper understanding for marketing practitioners and culinary business owners in formulating effective communication strategies in the digital environment.